Changes and significance of serum monocyte chemoattractant protein-1 and Lp-PLA2 in patients with hypertension and coronary heart disease - Tian, Yongbo; Fan, Yanhong; Chen, Li; Sun, Min (Journal of the Pakistan Medical Association, 2022)
Objective: To explore the combined application value of serum monocyte chemoattractant protein-1 and lipoprotein-associated phospholipase A2 in the diagnosis of hypertension and coronary heart disease. Methods: The cross-sectional case-control study was conducted at Baoji Hospital of Traditional Chinese medicine, Shaanxi, China, from April 2018 to May 2020, and comprised patients with suspected hypertension and coronary heart disease. Patients with both hypertension and coronary heart disease formed Group A, and those with simple hypertension formed Group B. Healthy individuals formed the control Group C. Receiver operating characteristic curve was used to evaluate the value of serum monocyte chemoattractant protein-1 combined with lipoprotein-associated phospholipase A2 in the diagnosis of hypertension complicated with coronary heart disease. Data was analysed using SPSS 25. Result: Of the 306 subjects, there were 122(40%) in Group A; 68(55.7%) males and 54(44.3%) females with mean age 68.77±5.76 years. There were 92(30%) cases in Group B; 51(55.4%) males and 41(44.6%) females with mean age 68.80±5.28 years. Group C had 92(30%) cases; 50(54.3%) males and 42(45.7%) females with mean age 67.85±5.29 years. Serum monocyte chemoattractant protein-1 and lipoprotein-associated phospholipase A2 levels were higher in Group A than the other two groups (p<0.001), and the levels in patients with carotid plaque total score <2 were lower than those with carotid plaque total score 2 (p<0.001). Area under receiver operating characteristic curve of the combination of the serum markers was 0.883 (95% confidence interval: 0.837-0.929, p<0.001), which was greater than that of two serum markers alone (p<0.05). —Continue